Home Musical Activities Boost Premature Infants' Language Development - Fabia Franco; Maria Chifa; Nina Politimou (MDPI AG, 2024)
Infants born prematurely are considered at risk for language development delay and impairments. Using online parental reports, the present study investigated the influence of early musical experience in the home environment (Music@Home Infant Questionnaire) on language development (MacArthur-Bates Communicative Development Inventory) while controlling for general enrichment at home (Stim-Q Cognitive Home Environment Questionnaire) and perinatal post-traumatic stress disorder (Perinatal PTSD Questionnaire). Caregivers of 117 infants between 8 and 18 months of age (corrected age) without reported developmental difficulties completed an online survey. Results revealed that the musical home environment significantly predicted outcomes in reported infants' receptive vocabulary and gestural communication, independently from infants' corrected age and general enrichment of home activities. These findings constitute the first evidence that an enriched musical experience can enhance the development of early communication skills in a population at risk for language delays, namely infants born prematurely, opening the path for future intervention research in home and/or early childcare settings. Given that the majority of participants in this study were highly educated and from socioeconomically stable backgrounds, considerations regarding the generalizability of these results are discussed.